Plant invaders the threat to natural ecosystems - Cronk, Quentin C. B.; Fuller, Janice L. (People and plants' conservation manuals, 1995)
As with each of the books in the series, Plant Invaders: The threat to natural ecosystems aims to give an authoritative account of the subject in a jargon-free style. It should therefore be of interest not only to the biologists studying plant invasion, but also to land managers and others concerned with practical conservation. Case studies of invasive species highlight specific problems from a wide range of countries, including North America, Africa, Australia, South and South East Asia, Europe, and the Pacific and Atlantic islands. The book contains an invaluable list of invasive species with their countries of origin and regions of introduction. A full bibliography carries references to all cited articles and books.